2019
DOI: 10.3389/fphar.2019.01169
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Actionable Pharmacogenetic Markers in Natives and Mestizos From Mexico

Abstract: The identification and characterization of pharmacogenetic variants in Latin American populations is still an ongoing endeavor. Here, we investigated SNVs on genes listed by the Pharmacogenomics Knowledge Base in 1284 Mestizos and 94 Natives from Mexico. Five institutional cohorts with NGS data were retrieved from different research projects at INMEGEN, sequencing files were filtered for 55 pharmacogenes present in all cohorts to identify novel and known variation. Bioinformatic tools VEP, PROVEAN, and FATHMM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
2
11
1
1
Order By: Relevance
“…Our results suggested that a significant number of the detected variants were rare, which is in concordance with findings from different population studies of pharmacogenes using NGS 34,35 . A high percentage of these rare variants were novel.…”
Section: Discussionsupporting
confidence: 91%
“…Our results suggested that a significant number of the detected variants were rare, which is in concordance with findings from different population studies of pharmacogenes using NGS 34,35 . A high percentage of these rare variants were novel.…”
Section: Discussionsupporting
confidence: 91%
“…The investigation of variants in 12 CYP genes revealed that the majority of variants are remarkably rare in both African-American and European-American ancestries 25 . Additionally, a large proportion of rare alleles with the potential to impact drug metabolism has been documented in Slovenian and Latino populations 26 , 27 . This is also supported by the investigation of individual variants by sequencing drug target genes, which demonstrated that rare variants are abundant in humans, and many have potentially relevant effects on drug metabolism 25 , 28 , 29 .…”
mentioning
confidence: 99%
“…Microarray genotyping technology eliminates the possibility of finding new variants in these pharmacogenes, but this could be accomplished with other techniques, such as next-generation technologies (NGS). An analysis of the Mexican population recently performed utilizing NGS found novel variation for some pharmacogenes between NA and MM populations (Gonzalez-Covarrubias et al, 2019). However, that analysis considered the MM population as a single group: an analysis of admixture patterns within the MM population, as performed in the present study, could be applied using NGS to refine the analysis of the Mexican population, and genomic guided some public health decisions in Mexico.…”
Section: The Pharmacogenetic Counseling Based On These Variants Could Depend On the Admixture Pattern Found In Different Geographical Regmentioning
confidence: 86%
“…The admixture of the Mexican population has been divided into two populations: Native Americans (NA) and Mexican Mestizos (MM) (Wang et al, 2008;Moreno-Estrada et al, 2014). There have been some attempts to identify how variants in the NA population affect pharmacology (Gonzalez-Covarrubias et al, 2016;Romero-Hidalgo et al, 2017;Gonzalez-Covarrubias et al, 2019), but in many analyses the entire MM population is grouped together, with no estimation of how admixture patterns within that group could affect the frequency of actionable pharmacogenetic variants or clinical counseling.…”
Section: The Pharmacogenetic Counseling Based On These Variants Could Depend On the Admixture Pattern Found In Different Geographical Regmentioning
confidence: 99%
See 1 more Smart Citation